Pengaruh Ukuran Butiran Pasir Vulkanik dengan parameter BOD dan COD pada Black Water menggunakan Metode Saringan Pasir Lambat - Presi Rishalehesty (Jurnal Migasian, 2022)
Indonesia has one of the lowest levels of sewerage connection and sanitation coverage in Asia. Gunung Kidul region in the D.I. Yogyakarta Province is one good example to describe realistic poor sanitation and sewage condition in Indonesia. This study intends to seek for the most suitable method to reuse liquid phase from septic tanks to become acceptable irrigation water. In advance, detailed objectives of this study are to identify the effect of grain size of sand filter on COD, BOD, Ammonia, Nitrate and E-Coli of the filtered black water. Materials in this research are Septic tank effluent taken from IPAL Sewon, grain size classified into three different size, medium, coarse and very coarse. The results of this study showed that medium grain size (-30+50 mesh) is the best sand type and grain size to utilize black water for irrigation.